Generation of four human-derived iPSC TorsinA-3xFLAG reporter lines from a DYT-TOR1A patient - Kerstin Tanzer; Britta Meier; Franca Vulinovic; Heike Pawlack; Christine Klein; Philip Seibler; Aleksandar Rakovic (Stem Cell Research)
A 3-bp deletion (ΔGAG) in TOR1A is a common cause of early-onset isolated dystonia DYT-TOR1A. The exact disease mechanism remains unknown. Here we describe the generation and characterization of four TorsinA-3xFLAG reporter induced pluripotent cell (iPSC) lines derived from a DYT-TOR1A patient. The cell lines carry either a ΔGAG variant or a corrected allele and a mono- or biallelic 3xFLAG-Tag introduced using CRISPR/Cas9 technology. These cells provide an opportunity to study differential protein stability, subcellular localization, and interactors of endogenous WT or ΔE variants of TorsinA in iPSCs, neural progenitor cells (smNPC), and neurons.